On maximum cycle packings in polyhedral graphs - Peter Recht; Stefan Stehling (Electronic Journal of Graph Theory and Applications (EJGTA), 2014)
This paper addresses upper and lower bounds for the cardinality of a maximum vertex-/edge-disjoint cycle packing in a polyhedral graph G. Bounds on the cardinality of such packings are provided, that depend on the size, the order or the number of faces of G, respectively. Polyhedral graphs are constructed, that attain these bounds.